Gut Microbiome and Pulmonary Arterial Hypertension - A Novel and Evolving Paradigm - Thenappan, T; Weir, E K (Physiological research, 2024)
Pulmonary arterial hypertension is characterized by perivascular and systemic inflammation. The gut microbiome influences the host immune system. Here we review the emerging preclinical and clinical evidence that strongly suggests that alterations in the gut microbiome may either initiate or facilitate progression of established pulmonary arterial hypertension by modifying the systemic immune responses. We also briefly review the relationship between the gut microbiome and preeclampsia, a vascular disease also characterized by inflammation. Key words: Dysbiosis, Right ventricle, Inflammation.
Keywords: Gastrointestinal Microbiome; Pregnancy; Humans; plicní arteriální hypertenze; Female; Inflammation; lidé; zvířata; Hypertension, Pulmonary; zánět; dysbióza; Pre-Eclampsia; Pulmonary Arterial Hypertension; plicní hypertenze; ženské pohlaví; Dysbiosis; preeklampsie; těhotenství; střevní mikroflóra; Animals